The estimation of potential of productive process of enterprise - Мастепан, Сергій Миколайович; Кузьмін, Віктор Степанович; Пащенко, Тетяна Володимирівна (Eastern-European Journal of Enterprise Technologies, 2012)
We consider a general approach to the assessment of production potential. The algorithm and mathematical model-building process to determine the components of: resource provision, the level of material and technical base, the degree of cooperation, professional level of employees is engineered